AKTIVITAS BIOSURFAKTAN DARI BAKTERI LUMPUR MINYAK MFS3 - Fifi Afiati; Martha Sari; Wien Kusharyoto (Universitas Sebelas Maret, 2014)
Abstract-The biosurfactant activity are surface active compound produced by microorganism, these molecules reduce surface tension between aqueous solutions that diverse of polarity. Endophytic bacteria MFS3, isolated from sludge oil resources presented positive biosurfactant test. The aim of this study is to screen of biosurfactant activity from MFS3 endophytic bacteria, by using Parafilm hydrophobic M test and surface tension determination by using Du-Nouy-ring Tensiometer method. The stability of surface tension curve in culture medium was stable for 8 days at 300C. Keywords: MFS3 bacteria, microscopy, surface tension, and parafilm M test